(untitled) (Al-Academy, 2015)
The art has been turned its subject in the post modern thinking . this turning is aresult to the turning in the role of the art it self. Across its history the art was basing its subject on a universal unite it the phenomenenon which is the most elevated . that the artist try to activate the role of the subject as a axial which compose the plastic art them. Because of the history of art full with subjects which consider in alarg part of it, have relation ship with elite and aesthetics , and from the begening of renaissance the central activity of the art was based on opoint which has concentrated reaction or it going in away belong to the state in that time.so renaissance was in relegous axial and romantisim on a dream axial, classisisim searching in luxe, imprissionlism based on the beauty of landscape and the natue changing.But in the post modernity , ther is another program which is the art left is articalchracteristic to the general charastristic , and try to destroy it